P555 Deep remission and mucosal healing in IBD patients under immunosuppression with azathioprine and 6-mercaptopurine. (25th January 2019) - Silva, J C; Silva, A P; Rodrigues, A; Fernandes, C; Ponte, A; Rodrigues, J; Sousa, M; Gomes, A C; Carvalho, J
Abstract: Background: Mucosal healing and deep remission (DR) are therapeutic targets in inflammatory bowel disease (IBD). We aimed to characterise DR in patients with Crohn's Disease (CD) and ulcerative colitis (UC) under monotherapy with immunomodulators. Methods: Out of a total of 432 patients observed in 2017–2018, 45 were under azathioprine or 6-mercaptopurine monotherapy for a period ≥3–6 months. Patients who underwent surgery, patients previously treated with anti-TNF and patients who started anti-TNF were excluded. DR was defined by: clinical remission (CR) in patients without endoscopically documented ulcers / erosions. Imaging activity was also evaluated in patients with CD. Results: Mean age was 37.9 ± 12.4 years and 53.3% were men. Of the 45 studied patients, 33 had CD (76.8%) and 12 UC (23.2%). In the group with CD Montreal Classification was evaluated (A2–90.9%, L1–39.4%, B1–78.8%), and in this group the prevalence of perianal disease and penetrating phenotype was 27.3% and 12.1%, respectively. In UC 75.0% had extensive colitis-E3. The mean age of diagnosis was 28.9 ± 11.0 years and the mean duration of the disease was 8.9 ± 6.8 years. The majority of patients were under azathioprine (93.3%). Mean duration of treatment was 5.15 ± 3.98 years. CR was obtained in 37 patients (CD-89.7%, CU-66.7%) and DR in 25 (DC-57.6%, CU-50.0%). Age of diagnosis, early-onset and duration of immunomodulatory treatment were not associated with DR. In CD, ileal disease, penetrating phenotype, and perianal disease showed no significant association with DR. The need for topical/oral corticosteroids after initiation of treatment was significantly associated with lower mucosal healing rates (p = 0.033). Conclusions: Despite the high rate of clinical remission under immunomodulator in monotherapy, about half of the patients did not achieved deep remission. The need for corticoid was associated with a lower probability of mucosal healing.